Activity of afatinib in patients with NSCLC harboring novel uncommon EGFR mutations with or without co-mutations: a case report - Christopoulos, Petros; Herster, Franziska; Hoffknecht, Petra; Falk, Markus; Tiemann, Markus; Kopp, Hans-Georg; Althoff, Andre; Stammberger, Anja; Laack, Eckart (Frontiers in Oncology, 2024)
Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) represent first-line standard of care in unresectable EGFR mutation-positive (EGFRm+) non-small cell lung cancer (NSCLC). However, 10–20% of patients with EGFRm+ NSCLC have uncommon EGFR variants, defined as mutations other than L858R substitutions or exon 19 deletions. NSCLC harboring uncommon EGFR mutations may demonstrate lower sensitivity to targeted agents than NSCLC with L858R or exon 19 deletion mutations. Prospective clinical trial data in patients with NSCLC uncommon EGFR mutations are lacking. Afatinib is a second-generation TKI and the only Food and Drug Administration-approved drug for some of the more prevalent uncommon EGFR mutations. We present a series of seven case reports describing clinical outcomes in afatinib-treated patients with NSCLC harboring a diverse range of extremely rare mutations with or without co-mutations affecting other genes. EGFR alterations included compound mutations, P-loop αC-helix compressing mutations, and novel substitution mutations. We also present a case with NSCLC harboring a novel EGFR::CCDC6 gene fusion. Overall, the patients responded well to afatinib, including radiologic partial responses in six patients during treatment. Responses were durable for three patients. The cases presented are in line with a growing body of clinical and preclinical evidence that indicating that NSCLC with various uncommon EGFR mutations, with or without co-mutations, may be sensitive to afatinib.